Effects of different training modalities on phosphate homeostasis and local vitamin D metabolism in rat bone - Buskermolen, Joost; van der Meijden, Karen; Furrer, Regula; Mons, Dirk-Jan; van Essen, Huib W.; Heijboer, Annemieke C.; Lips, Paul; Jaspers, Richard T.; Bravenboer, Nathalie (PeerJ, 2019)
Objectives Mechanical loading may be an important factor in the regulation of bone derived hormones involved in phosphate homeostasis. This study investigated the effects of peak power and endurance training on expression levels of fibroblast growth factor 23 (FGF23) and 1α-hydroxylase (CYP27b1) in bone. Methods Thirty-eight rats were assigned to six weeks of training in four groups: peak power (PT), endurance (ET), PT followed by ET (PET) or no training (control). In cortical bone, FGF23 was quantified using immunohistochemistry. mRNA expression levels of proteins involved in phosphate and vitamin D homeostasis were quantified in cortical bone and kidney. C-terminal FGF23, 25-hydroxyvitamin D3, parathyroid hormone (PTH), calcium and phosphate concentrations were measured in plasma or serum. Results Neither FGF23 mRNA and protein expression levels in cortical bone nor FGF23 plasma concentrations differed between the groups. In cortical bone, mRNA expression levels of sclerostin (SOST), dental matrix protein 1 (DMP1), phosphate-regulating gene with homologies to endopeptidases on the X chromosome (PHEX) and matrix extracellular phosphoglycoprotein (MEPE) were lower after PT compared to ET and PET. Expression levels of CYP27b1 and vitamin D receptor (VDR) in tibial bone were decreased after PT compared to ET. In kidney, no differences between groups were observed for mRNA expression levels of CYP27b1, 24-hydroxylase (CYP24), VDR, NaPi-IIa cotransporter (NPT2a) and NaPi-IIc cotransporter (NPT2c). Serum PTH concentrations were higher after PT compared to controls. Conclusion After six weeks, none of the training modalities induced changes in FGF23 expression levels. However, PT might have caused changes in local phosphate regulation within bone compared to ET and PET. CYP27b1 and VDR expression in bone was reduced after PT compared to ET, suggesting high intensity peak power training in this rat model is associated with decreased vitamin D signalling in bone.
Keywords: FGF23; Exercise; Phosphate homeostasis; Vitamin D; 1α-hydroxylation; Rat; Bone; Mechanical loading